Elevated carcinoembryonic antigen predicts rapidly progressive interstitial lung disease in clinically amyopathic dermatomyositis. (5th January 2021) - Zhu, Dingxian; Qiao, Jianjun; Tang, Shunli; Pan, Yunlei; Li, Sheng; Yang, Changyi; Fang, Hong
Abstract: Objectives: The present study aimed to determine the correlation between serum carcinoembryonic antigen (CEA) level and the severity of interstitial lung disease (ILD) in clinically amyopathic DM (CADM) patients. Methods: We performed a retrospective study including 41 Chinese CADM patients without malignancy. Serum CEA levels, clinical and laboratory findings were collected. Association tests between CEA levels and disease activity parameters were performed. Results: Among the 41 patients, 16 (39.0%) developed rapidly progressive (RP)-ILD; of them, 14 (87.5%) had elevated serum CEA levels. Multivariate logistic regression analysis indicated that an elevated serum CEA level was an independent risk factor for RP-ILD. The incidence of elevated CEA level was significantly higher in patients with RP-ILD than in those without RP-ILD (87.5 vs 16.0%, P  < 0.001). Furthermore, CEA levels were higher in patients with CADM with RP-ILD [26.87 (6.71) μg/l] than in those without RP-ILD [3.23 (0.64) μg/l] ( P  < 0.001). CEA levels in CADM patients were associated with the ferritin, alanine aminotransferase, aspartate aminotransferase and lactate dehydrogenase levels, and CT scores of the lungs. Also, elevated CEA levels are related to the organizing pneumonia pattern and lower lung zone consolidation in high-resolution CT. Moreover, the cumulative survival rate was significantly lower (68.4 vs 31.6%, P  < 0.001) in the group with a CEA level >8.75 μg/l than that in the group with a CEA level <8.75 μg/l. Conclusions: An elevated serum CEA level is common in patients with CADM, and a higher serum CEA level is a powerful indicator of RP-ILD and poor prognosis in those patients.